2014
DOI: 10.1016/j.jvs.2014.08.060
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Short Musculoskeletal Function Assessment in patients with battlefield-related extremity vascular injuries

Abstract: Use of the SMFA is validated in those with extremity vascular injuries, and it should be considered an adjunctive tool in evaluating long-term patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…The convergent-divergent validity of SMFA has been evaluated with a large variety of validated measures. 6,28,30,32,34,3945,67 As expected, the SMFA’s dysfunction index correlates highly with 14 out of 17 scales or subscales of validated measures evaluating solely patients’ perceived ability to perform functional tasks. SMFA’s bother index correlates highly with seven out of fifteen of such measures and moderately with five of them.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…The convergent-divergent validity of SMFA has been evaluated with a large variety of validated measures. 6,28,30,32,34,3945,67 As expected, the SMFA’s dysfunction index correlates highly with 14 out of 17 scales or subscales of validated measures evaluating solely patients’ perceived ability to perform functional tasks. SMFA’s bother index correlates highly with seven out of fifteen of such measures and moderately with five of them.…”
Section: Resultssupporting
confidence: 74%
“…24 According to this criterion, MFA and both indexes of SMFA do not have any significant floor or ceiling effects when used to evaluate the current function of people with actual disability. 5,6,[25][26][27][28][29][30][31][32][33][34][35] As expected, some ceiling effect can however be observed when the SMFA is used in time points when participants do not have much disability such as before or a long time after an injury. [29][30][31]36 The number of missing items or incomplete questionnaires in the included studies appears adequately low for the MFA and SMFA.…”
Section: Content Validitysupporting
confidence: 65%
See 1 more Smart Citation
“…These military surgeons concluded that the MESS was not useful in battle-field related injuries. Additional studies on battlefield-related extremity vascular injuries did find that those with preserved limbs but high MESS scores (≥ 7) had higher levels of dysfunction as rated with the Short Musculoskeletal Function Assessment tool (15). …”
Section: Discussionmentioning
confidence: 99%
“…A study by Scott et al demonstrated the reliability of SMFA in evaluating vascular extremity injuries in the trauma setting for armed forces. 17,18 It has been noted that each of the scoring systems discussed in this review demonstrate variable degrees of floor and ceiling effects. 2,15,[19][20][21] For example, FADI was found in one study (Eechaute et al 2 ) to demonstrate both floor and ceiling effects, although in another study (Hale and Hertel 15 ), it only demonstrated a ceiling effect.…”
Section: Discussionmentioning
confidence: 99%